2018
DOI: 10.1016/j.ijppaw.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate and host body condition influence mite population growth in a wild bird-ectoparasite system

Abstract: Parasite populations are never evenly distributed among the hosts they infect. Avian nest ectoparasites, such as mites, are no exception, as their distribution across the landscape is highly aggregated. It remains unclear if this pattern is driven by differences in transmission events alone, or if the environment that parasites inhabit after transmission also plays a role. Here, we experimentally examined the influence of the post-transmission microclimate, nest characteristics, and host condition on ectoparas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 54 publications
1
25
0
1
Order By: Relevance
“…While some hollow trees and particularly cave roosts can be used by bats for hundreds of years, leaf tents are usually abandoned within weeks or months after construction (Kunz & Lumsden, ; Rodríguez‐Herrera et al, ). Persistent roosts probably also provide more stable micro‐environmental conditions that favor a successful development of parasites (Dube et al, ); however, no conclusive correlation has been shown so far for bat flies (Dittmar, Dick, Patterson, Whiting, & Gruwell, ; Lourenço & Palmeirim, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some hollow trees and particularly cave roosts can be used by bats for hundreds of years, leaf tents are usually abandoned within weeks or months after construction (Kunz & Lumsden, ; Rodríguez‐Herrera et al, ). Persistent roosts probably also provide more stable micro‐environmental conditions that favor a successful development of parasites (Dube et al, ); however, no conclusive correlation has been shown so far for bat flies (Dittmar, Dick, Patterson, Whiting, & Gruwell, ; Lourenço & Palmeirim, ).…”
Section: Discussionmentioning
confidence: 99%
“…By including intrinsic factors and habitat characteristics, we cover a wide range of variables known to affect parasitization by bat flies (Bolívar‐Cimé et al, ; Patterson, Dick, & Dittmar, ; Pilosof et al, ) with the aim of disentangling the effects of habitat fragmentation on the prevalence and intensity of parasitization. We expect that bats using more permanent roosting structures will harbor more bat flies as these offer more stable host populations (Patterson et al, ) as well as microclimatic conditions favoring parasite development (Dube, Hund, Turbek, & Safran, ). Female and juvenile bats should be infested with bat flies more often and in higher intensities as they roost predominantly in year‐round stable groups together with their offspring, offering parasites a reliable food source (summarized in Frank et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…When this interaction was significant, we used pairwise post hoc comparisons to determine how subspecies differed in parasite tolerance. Breeding site was included as a random effect in all models to control for the nonindependence of many nests within a breeding location (e.g., barn and bridge), and because factors such as colony size and abiotic nest conditions are likely to influence parasites, particularily nests parasites (Dube et al 2018). We also report the conditional r-squared value (R 2 c, associated with the fixed effects plus the random effects), for each model using the Multi-Model Inference package (Bartroń 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A strong effect of location and distance has been found at large scales (hundreds or thousands of km) where environmental conditions differ substantially (Gómez-Díaz et al 2008, Krasnov et al 2008. However, at smaller spatial scales the effect of locality on ectoparasites richness and abundances has been reported (Lareschi and Krasnov 2010) together with factors such as microclimate, habitat characteristics at mesoscale, or host-related features (Poulin 2004, Kleindorfer and Dudaniec 2009, Krasnov et al 2015, Kleindorfer et al 2016, Dube et al 2018. Given that water availability and moist habitats determine the distribution and abundance of biting midges, mosquitoes, and blackflies (Braverman et al 1974, Ferraguti et al 2016, and given the large interannual differences in precipitation, we expected some geographical pattern associated with the proximity of temporary water courses or ponds to some nests, at least in some year(s).…”
Section: Discussionmentioning
confidence: 99%